Management, Leadership and Decision-making during a Global Economic Crisis - Krauss, Yaron (Marketing & Menedzsment, 2019)
In the midst of the current global economic turbulence institutions face challenging questions every day. These insecurities regarding their strategy to stay afloat, (how to save market share, update the product portfolio, keep the customers etc.) can only be answered successfully if the relevant human resources are provided. Managerial skills, leadership and decision-making have never been so important in companies’ life. In the ever sharpening market competition only those can win advantages, who are not only there at the right time and right place but also has the ability to make the right decision, even within seconds, no matter how difficult it may be. This study gives a thorough overview of the key elements of such managers, and sheds the light on some useful leadership techniques that might come on handy in the near future.